2006
DOI: 10.1086/507681
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Status of Intrahepatic T Cells in Chronic Hepatitis C

Abstract: Polychromatic flow-cytometric assays were used to analyze paired intrahepatic and peripheral lymphocyte samples from 37 patients with chronic hepatitis C. Compared with peripheral cells, intrahepatic T cells were selectively enriched with CD45RO+ memory T cells but had a lower percentage of CD4+ T cells expressing the differentiation markers CD27 and CD28. The percentage of intrahepatic CD45RO+ and CD28+ T cells correlated with the degree of liver inflammation, which suggests that memory T cells at relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Even during strong cytolytic responses, HCV-specific type 1 T cells in the periphery have intrahepatic counterparts that produce type 2 cytokines (22). Similarly, bulk-stimulated intrahepatic CD4 ϩ and CD8 ϩ T cells from chronic patients produce less IFN-␥ than peripheral blood cells and, in the case of CD8 ϩ cells, lower levels of perforin (21), resembling Tc2 lymphocytes (84,85). These data hint at the presence of an elusive type 2 biasing factor in the HCV-infected liver or associated lymphoid tissues, and we suggest that this might include nonspecific effector T CO cells capable of exerting type 2 pressure on HCV-specific cells.…”
Section: Discussionmentioning
confidence: 99%
“…Even during strong cytolytic responses, HCV-specific type 1 T cells in the periphery have intrahepatic counterparts that produce type 2 cytokines (22). Similarly, bulk-stimulated intrahepatic CD4 ϩ and CD8 ϩ T cells from chronic patients produce less IFN-␥ than peripheral blood cells and, in the case of CD8 ϩ cells, lower levels of perforin (21), resembling Tc2 lymphocytes (84,85). These data hint at the presence of an elusive type 2 biasing factor in the HCV-infected liver or associated lymphoid tissues, and we suggest that this might include nonspecific effector T CO cells capable of exerting type 2 pressure on HCV-specific cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated reduced levels of granzyme B and perforin in CD161+ T cells. HCV‐specific T cells also show low expression (although maturation can occur upon in vitro culture) 7, 8, 33. It is possible that CD161+ T cells, though they are effector memory cells, may have relatively defective killing independent of HCV status.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic and splenic immune cells were prepared according to previous publications with several modifications . Briefly, mice were killed by inhalation of carbon dioxide, following which the abdomen of each animal was immediately opened and the spleen was collected and put in ice‐cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Intrahepatic and splenic immune cells were prepared according to previous publications with several modifications. [15][16][17] Briefly, mice were killed by inhalation of carbon dioxide, following which the abdomen of each animal was immediately opened and the spleen was collected and put in ice-cold PBS. Then 10 ml cold PBS (pH 7Á4) was injected via the right ventricle of the heart to perfuse the liver until this organ became blanched and swollen.…”
Section: Isolation Of Intrahepatic and Splenic Immune Cellsmentioning
confidence: 99%